Prebiotic consumption in pregnant and lactating women increases IL-27 expression in human milk. Issue 4 (30th September 2013) - Kubota, Takayuki; Shimojo, Naoki; Nonaka, Ken; Yamashita, Masakatsu; Ohara, Osamu; Igoshi, Yuka; Ozawa, Naoko; Nakano, Taiji; Morita, Yoshinori; Inoue, Yuzaburo; Arima, Takayasu; Chiba, Kohki; et al.
Abstract : The consumption of probiotics by pregnant and lactating women may prevent the onset of allergic disorders in their children by increasing the concentrations of immunoactive agents such as cytokines in breast milk. Prebiotics such as fructo-oligosaccharides (FOS) increase the number of beneficial organisms such as bifidobacteria. Thus, prebiotics may have an effect similar to that of probiotics. The objective of the present study was to carry out a comprehensive analysis of mRNA expression in human milk cells to identify changes in the concentrations of cytokines in breast milk after the consumption of FOS (4 g × 2 times/d) by pregnant and lactating women. The microarray analysis of human milk cells demonstrated that the expression levels of five genes in colostrum samples and fourteen genes in 1-month breast milk samples differed more than 3-fold between the FOS and control groups (sucrose group). The mRNA expression level of IL-27, a cytokine associated with immunoregulatory function, was significantly higher in 1-month breast milk samples obtained from the FOS group than in those obtained from the control group. In addition, the protein concentrations of IL-27 in colostrum and 1-month breast milk samples were significantly higher in the FOS group than in the control group. In conclusion, the consumption of FOS by pregnant and lactating women increases the production of IL-27 in breast milk. Future studies will address the association of this phenomenon with the onset of allergic disorders in children.